If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -19x + Q = -19 + P Reorder the terms: Q + -19x = -19 + P Solving Q + -19x = -19 + P Solving for variable 'Q'. Move all terms containing Q to the left, all other terms to the right. Add '19x' to each side of the equation. Q + -19x + 19x = -19 + P + 19x Combine like terms: -19x + 19x = 0 Q + 0 = -19 + P + 19x Q = -19 + P + 19x Simplifying Q = -19 + P + 19x
| 72x5/8 | | 27/36=3/4 | | 0.3x+0.1(100-x)=180 | | |4-42|/2 | | -4(22/55)-3(10/55) | | 3*6=9*o | | 10x+15=11x+14 | | 9(13t+11)= | | 10=5/3v | | 175m-75m+48000=51000-150m | | 12/20=3/5 | | 8(13+15B)= | | 30x+10(100-x)=180 | | 5/2y=40 | | 12(11r-10)= | | 4y+2z-x= | | 16t^2+8t-80=0 | | 3(9a-6)= | | 5(8b+10)= | | -(6x-(2x+9))=-4-(6(2x-4)-6x) | | 7(5+y)= | | 25/60=5/15 | | 1.2x+3.8=8.696 | | 4(c-9)=-24 | | Q=1640-20p | | 10x+9=2x+25 | | 37x+5=y | | q+72=36 | | -y=5x+7 | | 2/5x-12/5 | | x+2x+3x-3-8=6x-11 | | 5(3h+-2)=2(h+8) |